The Italian novella and Shakespeare's comic heroines - Walter, Melissa Emerson, 1967- (University of Toronto Press, 2019)
"Using a comparative, feminist approach informed by English and Italian literary and theatre studies, this book investigates connections between Shakespearean comedy and the Italian novella tradition. Shakespeare's comedies adapted the styles of wit, character types, motifs of enclosed spaces, and other narrative materials of the Italian tradition for the Elizabethan and Jacobean stage, and investigated social norms and roles through a conversation carried out in narrative and drama. Arguing that Shakespeare's comic heroines express the playwright's reading of the novella, particularly his comic vision at the turn of the seventeenth century, this book demonstrates how such a vision valued women's authority and consent in the comic conclusion. The representation of female authority in novella collections is complex and paradoxical, as the stories portray women not only in the roles of witty plotters and storytellers but also through a poetics of enclosed spaces - including trunks, chests, caskets, graves, cups, and beds. These spaces are not as confining or simple as they may first appear. The relatively open-ended rhetorical situation of early modern English theatre and the dialogic form and narrative material available in the novella tradition combine to help create the complex female characters in Shakespeare's plays and a new form of English comedy."--